Application of Variation Drill Method Assisted by Audiovisual Media in Improving Futsal Ball Passing Skills for Xi Mia 2 Class Students at SMA Negeri 11 Bengkulu City - D. Septoni; martiani martiani; D. Apriansyah (Penerbit Jurnal Indonesia, 2021)
This study aims to improve the passing skills of futsal in students of grade XI MIA 2 SMA Negeri 11 of Bengkulu City by applying the variation drill method assisted by audiovisual media. The research subjects were students of grade XI MIA 2 SMA Negeri 11 of Bengkulu City. The research instrument was an observation sheet and a test sheet. Observational data analysis technique used qualitative analysis. The test data were analyzed using the formula for the average score and the percentage of classical learning completeness. The calculation results state that in the first cycle through the futsal passing test with an average score of 6.8 with a success rate of 32.14% and the percentage of the class through the observation sheet of 45.24% and in the second cycle through the futsal passing test with the acquisition The average score is 8.4 with a success rate of 85.71% and the percentage of the class through the observation sheet is 87.26%, which means that there is a significant increase in students' passing skills in the learning process. Thus, the application of the variation drill method assisted by audiovisual media in grade XI MIA 2 SMA Negeri 11 of Bengkulu City.